Pendayagunaan Ekonomi Umat Melalui Workshop Optimalisasi Pengumpulan dan Penyaluran Zakat - Muhammad Khozin; Zaidan Rizqia Wilda; Alief Budiyono (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2025)
Based on data from the Central Bureau of Statistics, Kebumen is the number 1 poorest district in Central Java. With the establishment of zakat villages in several villages in Kebumen Regency, including in Sampang Village, Sempor Subdistrict, it is hoped that it can synergize with the local government in reducing poverty. With the establishment of Sampang village as a zakat village by the Ministry of Religion of the Republic of Indonesia, the KKN Group 1 UIN Saizu Purwokerto x UIN Gusdur Pekalongan team held a workshop on Optimizing Policy Management & Empowerment of Zakat Development with the intention of being the first step of UPZ Sampang village in optimizing the policy and management of zakat that will be undertaken. This activity was carried out in three stages, namely the preparation stage, the implementation stage and the evaluation stage. The preparation stage was carried out by interviewing the head of UPZ Sampang Village and preparing the equipment that would be needed, be it MMT, finding presenters and so on. The second stage is the implementation stage, in this stage the material is delivered directly by the head of the Religious Affairs Office of the Ministry of Religious Affairs of Sempor District. The last stage is the evaluation stage, this stage aims to evaluate the activities that have been carried out and provide future views that will be carried out.